Human mesenchymal stromal cells modulate T‐cell responses through TNF‐α‐mediated activation of NF‐κB. Issue 2 (4th December 2013) - Dorronsoro, Akaitz; Ferrin, Izaskun; Salcedo, Juan Manuel; Jakobsson, Emma; Fernández‐Rueda, Jon; Lang, Valérie; Sepulveda, Pilar; Fechter, Karoline; Pennington, Dan; Trigueros, César
<x xml:space="preserve">Abstract</x> Although mesenchymal stromal cells (MSCs) possess the capacity to modulate immune responses, little is known about the mechanisms that underpin these processes. In this study, we show that immunosupression is mediated by activation of nuclear factor kappa B (NF‐κB) in human MSCs. This pathway is activated by TNF‐α that is generated following TCR stimulation of T cells. Inhibition of NF‐κB through silencing of IκB kinase β or the TNF‐α receptor abolishes the immunosuppressive capacity of MSCs. Our data also indicate that MSC‐associated NF‐κB activation primarily leads to inhibition of T‐cell proliferation with little effect on expression of the activation markers CD69 and CD25. Thus, our data support the hypothesis that the TNF‐α/NF‐κB signalling pathway is required for the initial priming of immunosuppressive function in human MSCs. Interestingly, drugs that interfere with NF‐κB activation significantly antagonise the immunoregulatory effect of MSCs, which could have important implications for immunosuppression regimens in the clinic.